Social determinants of food insecurity experienced by Ecuadorian women during the COVID-19 pandemic of Summer 2020: an online survey at the individual level - Tannia Valeria Carpio Arias; Marta Guijarro-Garvi; Yadira Alejandra Morejón-Terán; María Teresa Ruíz-Cantero (Canadian Science Publishing, 2024)
The COVID-19 pandemic has amplified concerns about food insecurity, prompting its investigation. An online pilot survey anonymously gathered responses from a non-probabilistic sample of 2058 Ecuadorian women. The Food and Agriculture Organization's Food Insecurity Experience Scale was used to measure moderate or severe food insecurity (MSFI). Data quality was assessed using the Rasch item response theory model; this is a single-parameter logistic model that considers food insecurity severity as a latent trait. The analysis produced MSFI prevalence rates with 90% confidence level margins of error (90%MoE). The highest MSFI was found in women: lacking resources for personal expenses (29.53%, 90%MoE = 3.21) compared to those who had them (12.47, 90%MoE = 1.40); who live in the Amazon region (21.37, 90%MoE = 4.24) versus those living in Highlands (17.66%, 90%MoE = 1.77) or in Coast (13.44%, 90%MoE = 2.40); with three or more children (20.97%, 90%MoE = 4.71) against those without children (12.63%, 90%MoE = 3.57); who experienced income reduction during confinement (18.31%, 90%MoE = 2) compared to those who did not (15.71%, 90%MoE = 1.85); and who are rural (18.13%, 90%MoE = 2.83) versus urban residents (16.63%, 90%MoE = 1.55). This study highlights that the most vulnerable Ecuadorian women experienced the highest food insecurity levels during lockdown, emphasizing the need to consider the intersection between income and sociodemographic factors and their impact on women's food insecurity in future research and policymaking.